2002
DOI: 10.1042/bj20020038
|View full text |Cite
|
Sign up to set email alerts
|

TcGPXII, a glutathione-dependent Trypanosoma cruzi peroxidase with substrate specificity restricted to fatty acid and phospholipid hydroperoxides, is localized to the endoplasmic reticulum

Abstract: Until recently, it had been thought that trypanosomes lack glutathione peroxidase activity. Here we report the subcellular localization and biochemical properties of a second glutathione-dependent peroxidase from Trypanosoma cruzi (TcGPXII). TcGPXII is a single-copy gene which encodes a 16 kDa protein that appears to be specifically dependent on glutathione as the source of reducing equivalents. Recombinant TcGPXII was purified and shown to have peroxidase activity towards a narrow substrate range, restricted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
54
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 57 publications
1
54
0
Order By: Relevance
“…1). Previously, we have noted that other components of enzyme-mediated oxidative defense in trypanosomes share surprising similarity with their plant counterparts, including an ascorbate-dependent hemoperoxidase from T. cruzi (6,36). Genome analysis now strongly suggests that the presence of these and other ''plant-like'' enzymes, notably those involved in carbohydrate metabolism, represent evidence that trypanosomatids possessed a plastid at some point in their evolution (37).…”
Section: Discussionmentioning
confidence: 99%
“…1). Previously, we have noted that other components of enzyme-mediated oxidative defense in trypanosomes share surprising similarity with their plant counterparts, including an ascorbate-dependent hemoperoxidase from T. cruzi (6,36). Genome analysis now strongly suggests that the presence of these and other ''plant-like'' enzymes, notably those involved in carbohydrate metabolism, represent evidence that trypanosomatids possessed a plastid at some point in their evolution (37).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, GzmB both induces generation of superoxide anions and destroys parasite mechanisms to detoxify it. To assess the importance of crippling oxidative defense in parasite killing, we treated T. cruzi epimastigotes overexpressing SodB, APX, MPX, CPX or a glutathione peroxidase (GPX1 or GPX2) [17][18][19][20] with GzmB and GNLY and found that overexpression of any of these enzymes, but not their inactive mutants, significantly rescued T. cruzi from death both in vitro (Fig. 2g) and in vivo (Fig.…”
mentioning
confidence: 99%
“…However, other peroxidases may also complement the tryparedoxin peroxidases system in trypanosomatids, with non-selenium GPX homologues recently being characterized in T. cruzi (18) and T. brucei (14). Interestingly, the T. cruzi GPX II was reported to be reduced directly by GSH and not by TryX or T[SH] 2 (20). Moreover, GPX II appeared to be specific for fatty acid and lipid hydroperoxides and to be localized to the ER.…”
Section: Resultsmentioning
confidence: 99%
“…Initial studies showed the complex in the anterior of the parasite, particularly around the nucleus and kinetoplast. This pattern is characteristic of proteins located to the endoplasmic reticulum (ER) (20,39). Double labeling of parasites with anti-C. fasciculata eEF1B antiserum and an antiserum raised against the T. brucei homologue of the ER-localized chaperone BiP (39) was therefore performed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation